Eflfert of sulphur on yield attributes and yield of Indian mustard (Brassica juncea) as influenced by irrigation* - PIRI, ISSSA; SHARMA, S N (The Indian Journal of Agricultural Sciences, 2011)
A field experiment was carried out during rabi season of 2003-04 and 2004-05 to study the effect of levels of irrigation and sulphur on yield attributes and yield of Indian mustard (Brassica juncea L. Czernj & Cosson.). The results revealed that both irrigation and sulphur significantly increased the yield attributes and seed and straw yields of Indian mustard. The crop responded to sulphur differentially under different irrigation regimes. Without irrigation, seed yield of Indian mustard increased when rate of sulphur was increased from 0 to 45 kg Sha, whereas with 1 or 2 irrigations seed yield increased with 30 kg Siha.